English teacher personality and professionalism on tenth-grade student motivation at vocational schools - Indarti, Nunuk; Hasanah, Imroatul (EduLite: Journal of English Education, Literature and Culture, 2024)
This study aims to explore three main objectives: to assess the personality of English teachers involved in teaching and learning activities for tenth-grade students at vocational school in Pasuruan, East Java, to evaluate the professionalism of these teachers, and to measure the motivation of the students in the same context. The study focuses on all tenth-grade students at vocational school in Pasuruan, comprising 109 students across four classes. A quantitative descriptive method was employed to collect data using questionnaires. The instruments included a 26-item Teacher Personality Questionnaire and a 20-item Teacher Professionalism Questionnaire, both serving as independent variables, and a 26-item Student Motivation Questionnaire as the dependent variable. Multiple regression analysis was performed using SPSS Windows 25.0 to determine the influence of teacher personality and professionalism on student learning motivation. The results revealed that teacher personality had a more significant impact on student motivation (61.77%) compared to teacher professionalism (35.76%). Together, English teacher personality and professionalism accounted for 66% of the variance in student motivation, with the remaining 34% attributed to other factors. The study concludes that both English teacher personality and professionalism significantly influence student learning motivation. It is recommended that teachers not only focus on teaching and educating but also enhance their roles as motivators and supporters to better address and understand student needs.